2008
DOI: 10.3317/jraas.2008.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of losartan on exercise tolerance and echocardiographic parameters in patients with mitral regurgitation

Abstract: Paper AbstractObjectives. The aim of this study was to assess the effects of losartan treatment on exercise tolerance and echocardiographic parameters in patients with mitral regurgitation (MR) secondary to mitral valve prolapse or rheumatic heart disease. Methods. Twenty-seven patients (14 males, 13 females, mean age 51±11, range 21-76) with moderate MR due to mitral valve prolapse or rheumatic heart disease were examined by means of Doppler echocardiography.The subjects were submitted to treadmill exercise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Sekuri et al . 23 found that losartan can improve the exercise tolerance and echocardiographic parameters in patients with rheumatic mitral regurgitation (MR) disease. Compared with rheumatic mitral valve disease, rheumatic aortic or tricuspid valve diseases are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekuri et al . 23 found that losartan can improve the exercise tolerance and echocardiographic parameters in patients with rheumatic mitral regurgitation (MR) disease. Compared with rheumatic mitral valve disease, rheumatic aortic or tricuspid valve diseases are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Chockalingam et al 22 found that enalapril not only was well tolerated but also improved functional status and exercise capacity in RHD patients with moderate and severe mitral stenosis (MS), especially in patients with concomitant regurgitant valvular heart disease. Sekuri et al 23 found that losartan can improve the exercise tolerance and echocardiographic parameters in patients with rheumatic mitral regurgitation (MR) disease. Compared with rheumatic mitral valve disease, rheumatic aortic or tricuspid valve diseases are rare.…”
Section: Effect Of Renin-angiotensin-aldosterone System Inhibitor Tre...mentioning
confidence: 99%
“…Specifically, the regurgitant volume and the effective regurgitant orifice decreased and the effect was durable for 1 month [15]. Another trial assessing moderate degenerative and rheumatic MR also found a beneficial effect with losartan over a 6-week period with regards to MR severity, LA size, and LV function [23].…”
Section: Vasodilators In Chronic Mitral Regurgitationmentioning
confidence: 92%
“…13 Diuretic therapy is indicated for management of volume and symptoms but has not been found to result in survival benefit. 14 By the reduction of left ventricular afterload, angiotensin-converting enzyme inhibition improves exercise tolerance and echocardiographic indices in severe mitral regurgitation, and is particularly beneficial in the setting of concomitant systemic hypertension, 15 but it has yet to be found to confer a definite survival benefit. The patient's CHA 2 DS 2 -VASc score is 5, with points assigned for heart failure, hypertension, age, and sex.…”
Section: Which One Of Thementioning
confidence: 99%